2021
DOI: 10.1097/ju.0000000000002121
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Metastatic Castration-Sensitive Prostate Cancer in the Real-World Setting in the United States

Abstract: This study provides a contemporary assessment of the treatment patterns, healthcare resource utilization (HRU), and costs among metastatic castration-sensitive prostate cancer (mCSPC) patients in the US.Methods: Adults with mCSPC were selected from Optum's de-identified Clinformatics® Data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…Upfront intensification not only prolongs life but does so without compromising quality-of-life as observed in randomized clinical trials [13]. However, retrospective studies (mostly as abstracts) from multiple different databases including Optum, Medicare and ConcertAI Oncology Dataset have shown a consistent underutilization of intensification ranging from < 10% to up to 30% of mCSPC patients and even those with visceral disease and in those with insurance [14][15][16][17]. In our dataset, we confirm that upfront intensification was low but a gradual and encouraging trend towards increased intensification was observed over the last 5 years (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Upfront intensification not only prolongs life but does so without compromising quality-of-life as observed in randomized clinical trials [13]. However, retrospective studies (mostly as abstracts) from multiple different databases including Optum, Medicare and ConcertAI Oncology Dataset have shown a consistent underutilization of intensification ranging from < 10% to up to 30% of mCSPC patients and even those with visceral disease and in those with insurance [14][15][16][17]. In our dataset, we confirm that upfront intensification was low but a gradual and encouraging trend towards increased intensification was observed over the last 5 years (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, second generation anti‐androgens, including abiraterone acetate, apalutamide and enzalutamide, have conferred an additional survival benefit when combined with ADT, and also concurrent with docetaxel as trimodal therapy in select patient groups 67,87 . Despite this, many Australian men only receive ADT as primary management for mHSPC 88 . For men with de novo low volume disease, high dose palliative radiotherapy to the prostate also confers an overall survival benefit 74 …”
Section: Advanced Prostate Cancermentioning
confidence: 99%
“…67,87 Despite this, many Australian men only receive ADT as primary management for mHSPC. 88 For men with de novo low volume disease, high dose palliative radiotherapy to the prostate also confers an overall survival benefit. 74 The treatment landscape has vastly changed for mCRPC, defined as biochemical or radiological progression despite castrate serum testosterone levels (< 50 ng/dL or < 1.75 nmol/L).…”
Section: Narrative Reviewmentioning
confidence: 99%
“…The real-world data of mHNPC in the U.S., the highest GDP ranked country, demonstrated that the usage of abiraterone was 10% in 2019 and ARATs was 17% in 2020, while around 50% of mHNPC patients still received ADT monotherapy, 5 partially due to the high cost of the drug that will not be covered by the private healthcare system. 5 In the next few years, several novel therapies such as immuno-oncology drug, genome-based companion drugs, and prostate specific membrane antigen based therapy will be introduced on the market in mHNPC. It will be ideal to establish the treatment strategies of mHNPC based on prognosis and cost that will fit among the Asian prostate cancer population to attain the sustainable development goals.…”
Section: Editorial Commentmentioning
confidence: 99%